Emprego da microextração líquido-líquido dispersiva em fase reversa para o preparo de amostras de óleo de palma e posterior determinação de cádmio, chumbo e cobre por espectrometria de absorção atômica com chama - Leonardo, Brucy Fraga (2024)
Palm oil has gained prominence in the global industry, especially in the food sector, due to its physicochemical properties. It has been replacing soybean oil in the food industry. This vegetable oil can be found in food products such as biscuits, pasta, and many other items that are part of our daily diet. Palm oil is composed of monounsaturated fatty acids and natural antioxidants, making it capable of withstanding high temperatures, as well as linoleic acid, an important natural antioxidant that preserves the quality of palm oil by preventing lipid oxidation. The determination of contaminants in palm oil samples is crucial to ensuring food safety, as well as maintaining the quality of this vegetable oil and extending its shelf life, preventing lipid oxidation caused by contaminants that are considered bioaccumulative in the human body. In this study, the reverse-phase dispersive liquid-liquid microextraction (RP-DLLME) method was employed for sample preparation, preconcentration, and extraction of Cd, Pb, and Cu elements in palm oil. Triplicate tests were conducted on palm oil samples with the addition of 1 μg g-1 of analytes, using a standard solution in an organic medium. The determination of the analytes was carried out by flame atomic absorption spectroscopy (F AAS) with external calibration. To optimize the proposed method, several parameters were evaluated: sample mass (5 g), diluent solvent (D-limonene), type of extractor solvent (HNO3), type of disperser solvent (n-propanol), ratio of disperser and extractor solvents, extract solvent concentration, temperature, agitation, and centrifugation. The recovery values for Cd, Cu, and Pb analytes ranged from 90% to 102%, with RSD values < 5%. Furthermore, the LOQ and LOD values were validated within the parameters required by ANVISA. The best results were obtained using 1 mL of a solution containing 1 molar HNO3 as the extracting agent and n-propanol as the dispersing agent in a 70:30 v/v ratio, with heating in a water bath for 10 minutes at a temperature of 80 °C and centrifugation for 10 min at 6000 rpm. This method did not require sample digestion with acidic solvents or combustion and offers operational simplicity, lower reagent consumption, and relatively low costs. Additionally, it aligns with the principles of green analytical chemistry.